Complex Metabolic Phenotypes Caused by a Mutation in yjgF, Encoding a Member of the Highly Conserved YER057c/YjgF Family of Proteins - Enos-Berlage, Jodi L. (American Society for Microbiology, 1998)
The oxidative pentose phosphate pathway is required for function of the alternative pyrimidine biosynthetic pathway, a pathway that allows thiamine synthesis in the absence of the PurF enzyme in Salmonella typhimurium. Mutants that no longer required function of the oxidative pentose phosphate pathway for thiamine synthesis were isolated. Further phenotypic analyses of these mutants demonstrated that they were also sensitive to the presence of serine in the medium, suggesting a partial defect in isoleucine biosynthesis. Genetic characterization showed that these pleiotropic phenotypes were caused by null mutations in yjgF, a previously uncharacterized open reading frame encoding a hypothetical 13.5-kDa protein. The YjgF protein belongs to a class of proteins of unknown function that exhibit striking conservation across a wide range of organisms, from bacteria to humans. This work represents the first detailed phenotypic characterization of yjgF mutants in any organism and provides important clues as to the function of this highly conserved class of proteins. Results also suggest a connection between function of the isoleucine biosynthetic pathway and the requirement for the pentose phosphate pathway in thiamine synthesis.